Synthesis of Multisubstituted Benzenes from Phenols via Multisubstituted Benzynes - Nagai, Akira; Kobayashi, Akihiro; Sakata, Yuki; Minami, Yasunori; Uchida, Keisuke; Hosoya, Takamitsu; Yoshida, Suguru (Synthesis, 2022)
A new method to synthesize multifunctionalized arenes from simple phenols through aryne intermediates is described. Multisubstituted aryne precursors were prepared from phenols by Ir-catalyzed C–H borylation, deborylthiolation, O-triflylation, S-oxidation, and further modification through ortho-deprotonation directed by the sulfoxide moiety. Various multisubstituted arenes were synthesized by transformations of highly functionalized aryne intermediates generated from the o-sulfinylaryl triflates.
Keywords: aryne intermediates; sulfoxides; Knochel–Hauser base; Grignard reagents; triazoles